Assessing cloud computing security level of awareness among IT and non IT students in UTM - Mohammed, Alwuhayd Muteb (2014)
The cloud computing service is a new paradigm for providing storage and application on demand by using internet. While clouds computing becoming one of the most growing services in information technology, people have expressed apprehensions regarding security aspects of this new model. However, the procedural and technical procedures on this service success is depends on users awareness about the security risk and their relations with the knowledge on it. In this research, issues in security awareness as an effect of user’s education background were being investigated. These issues cover three equivalent dimension namely behavior, attitude and knowledge regarding cloud service security. Each one of these dimensions was then subdivided into the three focus areas in cloud service usability, internet security and physical security. The data gathering is done by using questionnaire, involving three different faculty students as respondents, which are Faculty of Computing, Faculty of Education and Faculty of Bioscience and Medical Engineering. The technical expertise dimension is then divided into IT-related background in Faculty of Computing and non-IT related background in Faculty of Educations and Faculty Bioscience and Medical Engineering. This research involved 119 students from these three faculties. Results show a significant impact on cloud service usability and security knowledge on IT related background students. However, the total level awareness of IT related background are considered equal to non-IT related background students while their lower attitude on the security awareness tends to neglecting their knowledge to the impact of their unsecure behavior